2021
DOI: 10.2147/jaa.s328652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Pollutant Exposure on Exacerbation Severity in Asthma Patients with or without Reversible Airflow Obstruction

Abstract: Background Reversible airflow obstruction (RO) and fixed airflow obstruction (FO) are two important clinical phenotypes of asthma. However, the relationship between air pollutant exposure and exacerbation of the two phenotypes is unknown. Objective To study the effects of air pollutant exposure on exacerbation severity in asthma patients with or without FO. Methods A total of 197 severe asthma patients were enrolled, and divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Also, recording asthma triggers encountered, such as viral infections, passive smoke, and pets, could give a better understanding of a person's asthma and their symptoms. [64][65][66] Connecting data from pollution monitoring stations and meteorology stations with patient health records provides a wealth of information for analysis.…”
Section: Environment Monitoringmentioning
confidence: 99%
“…Also, recording asthma triggers encountered, such as viral infections, passive smoke, and pets, could give a better understanding of a person's asthma and their symptoms. [64][65][66] Connecting data from pollution monitoring stations and meteorology stations with patient health records provides a wealth of information for analysis.…”
Section: Environment Monitoringmentioning
confidence: 99%
“…We discovered no statistically significant difference in arterial blood gas analyses between the three groups of With a sensitivity of 36% and a specificity of 91.2%, a different study of adult asthmatic patients found that a concentration of 57.659 μg/ m 3 of PM2.5 (AUC = 0.645, p = 0.027) offered the highest performance to predict severe asthma exacerbation. 10 Our findings suggested that asthmatic youngsters may be more sensitive to elevated PM2.5 levels than adult asthmatics. When the ambient PM2.5 concentration is excessively high, asthmatic children should limit their outside activities to lower their risk of having severe asthma attacks.…”
Section: Discussionmentioning
confidence: 56%
“…The frequency of severe asthma exacerbation in children increased when the PM2.5 concentration rose beyond 44.5 μg/m 3 . With a sensitivity of 36% and a specificity of 91.2%, a different study of adult asthmatic patients found that a concentration of 57.659 μg/m 3 of PM2.5 (AUC = 0.645, p = 0.027) offered the highest performance to predict severe asthma exacerbation 10 . Our findings suggested that asthmatic youngsters may be more sensitive to elevated PM2.5 levels than adult asthmatics.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations